The Process of Social Adaptation of Preschool Children in Sports Sections (Schools) - Boxodirovna, Turakulova Durdona; Ubaydullayevna, Raxmonova Gulruh (European Journal of Life Safety and Stability (2660-9630), 2021)
The article examines the processes of social adaptation of preschool children during sports, the relationship and mutual understanding of children between coaches and parents during physical education, the influence of parents during the social adaptation of the child.